2018
DOI: 10.1108/nfs-01-2018-0027
|View full text |Cite
|
Sign up to set email alerts
|

Fortification of tempeh with encapsulated iron improves iron status and gut microbiota composition in iron deficiency anemia condition

Abstract: Purpose Iron deficiency anemia (IDA) is one of the most major micronutrient deficiencies worldwide. Food fortification is one strategy for reducing IDA in the population despite concern regarding the gut pathogenic bacteria overgrowth. The purpose of this study was to evaluate the effect of iron encapsulation in banana peel matrix on iron status and gut microbiota composition in iron deficiency anemia. Design/methodology/approach Anemia was induced in 35 male Sprague Dawley rats of age two weeks by the admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…The addition of 28 to 112 mg/kg of sodium ferric ethylenediaminetetraacetic acid (NaFeEDTA) before fermentation at 32 °C for 16 to 32 hr did not alter organoleptic properties and increased hemoglobin levels in female Wistar rats at 24 ppm more than supplementations of FeSO 4 and regular tempeh (Sudargo et al., 2015). Similar results were observed in anemic male Sprague–Dawley (SD) rats (Kusuma & Ermamilia, 2018). In tempeh made of 30 g of soybeans, fortification with 0.166% (w/w) of NaFeEDTA promoted iron (Fe) levels of 12.54 mg before cooking and 8.40 mg after boiling—meeting the recommended daily allowance (RDA) of 8 to 15 and 7.74 mg after frying (Mahardika et al., 2020).…”
Section: Resultssupporting
confidence: 78%
“…The addition of 28 to 112 mg/kg of sodium ferric ethylenediaminetetraacetic acid (NaFeEDTA) before fermentation at 32 °C for 16 to 32 hr did not alter organoleptic properties and increased hemoglobin levels in female Wistar rats at 24 ppm more than supplementations of FeSO 4 and regular tempeh (Sudargo et al., 2015). Similar results were observed in anemic male Sprague–Dawley (SD) rats (Kusuma & Ermamilia, 2018). In tempeh made of 30 g of soybeans, fortification with 0.166% (w/w) of NaFeEDTA promoted iron (Fe) levels of 12.54 mg before cooking and 8.40 mg after boiling—meeting the recommended daily allowance (RDA) of 8 to 15 and 7.74 mg after frying (Mahardika et al., 2020).…”
Section: Resultssupporting
confidence: 78%
“…The authors indicated that fortification of tempeh with encapsulated iron enhanced the iron status in iron deficiency anemia. 137 Darwish et al formed iron and folic acid (FA) in bovine serum albumin nanoparticles as antianemic pharmacological agents that fortify stirred functional yogurt (SFY). They compared these with a plain control and SFY fortified with iron in free forms.…”
Section: Recent Studies On Improving Iron Bioavailabilitymentioning
confidence: 99%
“…The hemoglobin and serum iron levels were the highest in iron-fortified tempeh with elemental iron dose + probiotic group (11.01 6 0.15 g/dl and 340.556 1.55 mg/dl, respectively) followed by encapsulated iron-fortified tempeh with an elemental iron dose group (10.71 6 0.15 g/dl and 338.07 6 4.17 mg/dl). The authors indicated that fortification of tempeh with encapsulated iron enhanced the iron status in iron deficiency anemia . Darwish et al formed iron and folic acid (FA) in bovine serum albumin nanoparticles as antianemic pharmacological agents that fortify stirred functional yogurt (SFY).…”
Section: Recent Studies On Improving Iron Bioavailabilitymentioning
confidence: 99%
“…Soybean was obtained from the local market. Tempeh was developed with modifications according to our previous study [23]. Briefly, the soybean was cleaned, washed, and immersed in distilled water for 2 h. The soybean was boiled for 15 min and dehulled.…”
Section: Preparation Of Modified Tempehmentioning
confidence: 99%